HCM Practices and its Impact on Turnover, Profitability, and Sustainability in the Indian Business Environment - Pandey, Vivek (Prabandhan: Indian Journal of Management, 2013)
Human Capital is the most important asset for any organization, and it is a unique source of achieving competitive advantage. Human Capital Management (HCM) practices refer to organizational activities directed at managing the pool of human resources and ensuring that the resources are employed by maximizing their competencies towards the fulfillment of organizational financial and non-financial goals. Competitive advantage of a company can be generated from human resources, and company performance is influenced by a set of effective HCM practices. 9 Industries, 23 Sectors, and 109 organizations across India were covered under the present study of HCM practices and related processes maturity to study its impact on turnover, profitability, and sustainability.